Epidemiological study of snakebite cases in brazilian western Amazonia - Roriz, Katia Regina Pena Schesquini (2018)
Introduction : Brazil has the largest number of snakebite cases in South America, of which the large majority is concentrated in the Midwest and North. Methods : In this descriptive observational study, we assessed the epidemiological and clinical snakebite cases referred to the Centro de Medicina Tropical de Rondônia from September 2008 to September 2010. Results : We followed up 92 cases from admission until discharge, namely 81 (88%) men and 11 (12%) women, with a mean age of 37 years, and mainly from rural areas (91.3%). The snakebites occurred while performing work activities (63%) during the Amazon rainy season (78.3%). The vast majority of individuals presented from the Porto Velho microregion (84.7%). Approximately 95.6% of the snakebites were caused by snakes of the genus Bothrops , followed by two lachetics and two elapidics cases. Surgery was performed in 10 cases (9 fasciotomies in the lower limb and 1 amputation). No deaths were reported in this study, but 4 cases (4.3%) developed sequelae in the lower limb. Conclusions : This study can contribute to a better understanding of envenomation in the state of Rondônia and thus can be useful for identifying real conditions that can increase the incidence of snakebites in this region. Moreover, the study results can serve as a basis for improving educational campaigns designed to prevent these types of snakebites, as well as for preserving snakes.